Experimental Study on Previous Concrete with Various Mix Ratios - Htay, Hla Hla; Aung, Htet Thu; Kyaw, Nyan Myint (Institut Teknologi Sepuluh Nopember, 2017)
The pervious concrete is designed with cementitious material content just enough to coat the coarse aggregate particles so that a configuration that allows the passage of water at a much higher rate than conventional concrete. The pervious concrete has many advantages that improves city environment, recharges the ground by rain water and could be used as pavement for light vehicles, pedestrian pathways, parking lots, also it reduces the tire pavement interaction noise etc. In this paper, structural property and permeability of pervious concrete made without and with different ratios of fine aggregate and pozzolan. 9.5 mm maximum size of crushed gravel and constant aggregate/cement ratio of 3.6 were used. Mix design void content is tested 20%. The specific gravity of fine aggregate 2.53 and the specific gravity of crushed stone 2.56. Type I Portland cement and water- reducing and retarding concrete admixture were used. Mix design is based on the no slump method from the American Concrete Instituteâ€™s Committee 211.3R-02, â€œStandard Practice for Selecting Proportions for No Slump Concrete.â€ This research work was divided into third/three sections. The first section is without pozzolan and fine aggregate and second section is with two different ratios of pozzolan third section is without pozzolan and with fine aggregate. Pozzolan is used as a supplementary cementitious material to partially replace Portland cement in pervious concrete mixes up to 20% by weight. Fine aggregate partially replace as a coarse aggregate in pervious concrete mixes up to 10% by weight. Mix design void content is tested 20%. This concrete is tested for its properties, such as density, void content, compressive strength and water permeability. The most important property of pervious concrete is its water permeability.